2020
DOI: 10.1002/elan.201900707
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Reduction of Oxygen at Glassy Carbon Electrodes Coated with Diazonium‐derived Porphyrin/Metalloporphyrin Films

Abstract: In this study, the influence of the film structure was investigated on the electrocatalytic oxygen reduction at GC electrodes covered with porphyrin and metalloporphyrin rings via the diazonium modification method. For that purpose, primarily, tetraphenylporphyrin (TPP) films on GC electrode surfaces were prepared by electroreduction of in situ generated diazonium salts of 5‐(4‐aminophenyl)‐10,15,20‐triphenylporphyrin (APP) and 5,10,15,20‐tetrakis(4‐aminophenyl)porphyrin (TAPP) molecules. Next, the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…130 Kudas et al compared the ORR in pH 7 buffer at surfaces modified with Fe-, Co-, and Mn-tetraphenylporphyrin (TPP) in the edge-on configuration and found that only FeTPP catalyzed the four-electron reduction. 132 Immobilized metal complexes can also catalyze the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Le Goff et al's hydrogenase mimic, a dithiolatebridged hexacarbonyldiiron complex, showed catalytic activity for HER in a strong acid but was rapidly deactivated.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…130 Kudas et al compared the ORR in pH 7 buffer at surfaces modified with Fe-, Co-, and Mn-tetraphenylporphyrin (TPP) in the edge-on configuration and found that only FeTPP catalyzed the four-electron reduction. 132 Immobilized metal complexes can also catalyze the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Le Goff et al's hydrogenase mimic, a dithiolatebridged hexacarbonyldiiron complex, showed catalytic activity for HER in a strong acid but was rapidly deactivated.…”
Section: Applicationsmentioning
confidence: 99%
“…Free-base porphyrins and Pcs can also be directly grafted from diazonium ion derivatives and subsequently metallized with various ions (Scheme ). There are several reports that grafted carboxyphenyl and amine groups can lead to the assembly of metal–organic frameworks (MOFs), presumably through an initial coordination of metal ions.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A literature survey on electrochemical reduction of diazonium salts show that the goal of most of these studies is the reduction of the diazonium salts to produce the corresponding radical in order to modify the electrode surface (Scheme 1). [13][14][15][16][17][18][19][20][21] These studies show that the reduction of aryldiazoniums involves a single-electron transfer from the cathode to the aryldiazonium salt, resulting in the release of a nitrogen molecule and the formation of an aryl radical followed by the bond formation between the electrode surface and the aryl group. Many researchers have worked on the graing of aryldiazonium salts on different electrode surfaces, and obtained satisfactory results.…”
Section: Introductionmentioning
confidence: 94%
“…and application of these electrografted tetraphenylporphyrin-based diazoniums towards the electrocatalytic reduction of oxygen [63].…”
Section: Electrografting Of Tetraphenylporphyrin-based Diazoniummentioning
confidence: 99%